"'Othering' with Grace and Courage": Reflections on the Dynamic Tension between Mutuality and Incommensurability. Issue 5 (25th February 2021) - Kärkkäinen, Veli‐Matti
Abstract: This essay considers the complexity and dynamic of seeking to balance an openness to the religious "other" and their beliefs with the honest acknowledgement of real and often deep incommensurability between one's own and the other's deepest convictions. This kind of hospitable and mutually edifying encounter is possible by putting into practice the method of comparative theology which, while urging the faithful in every tradition to establish their own religious identity, also facilitates learning from the other and makes room for sharing one's own testimony. Not only theological and confessional but also autobiographical and life narratives matter in this process.